Spread of Tomato yellow leaf curl virus Sar from the Mediterranean Basin Presence in the Canary Islands and Morocco - Monci, F (Plant disease, 2000)
Severe outbreaks of tomato yellow leaf curl disease occurred during summer and autumn 1999 in tomato (Lycopersicon esculentum Mill.) crops in the Vecindario Region of Gran Canaria (Canary Islands, Spain) and Agadir (southwestern Atlantic coast of Morocco). Symptoms of the disease included upward curling of leaflet margins, reduction of leaflet area, and yellowing of young leaves, as well as stunting and flower abortion. High populations of whiteflies, Bemisia tabaci Gen., were present on tomatoes in Agadir, and analysis of adult individuals by random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) identified them as the biotype Q. Samples were collected from symptomatic tomato plants: 5 plants from Gran Canaria and 22 from three areas in Agadir, (7 from Agadir/1, 12 from Agadir/2, and 3 from Agadir/3) in the Koudya Region. Samples were analyzed for Tomato yellow leaf curl virus (TYLCV) Sar or Is (genus Begomovirus, family Geminiviridae) infection by squash blot hybridization under high stringency conditions with digoxigenin-labeled DNA probes specific to TYLCV-Sar or -Is, as described previously (1,3). The TYLCV-Sar probe hybridized to the five samples from Gran Canaria, and the TYLCV-Is probe hybridized to the 22 samples from Agadir. The TYLCV-Sar probe also hybridized to the three samples from Agadir/3. Primer pairs MA-14/MA-15 and MA-30/MA-31, designed for specific amplification of the intergenic region (IR) of TYLCV-Sar or -Is reported from Spain, respectively (1), were used in PCR to amplify one sample each from Gran Canaria, Agadir/1, and Agadir/3. A fragment of the expected size was obtained from the samples from Gran Canaria and Agadir/3 using MA14/MA15 (342 bp) and from the two samples from Agadir using MA30/MA31 (357 bp). PCR products were directly sequenced (GenBank Accession nos. AF215819 to AF215822). The nucleotide sequences of the IR fragments amplified from the Gran Canaria and Agadir/3 sample using MA-14/MA-15 indicated their closest relationship (99.0 and 96.7% identity, respectively) was to the corresponding region of a TYLCV-Sar isolate reported from Spain (GenBank Accession no. L27708). The nucleotide sequences of the IR fragments amplified from the Agadir/1 and Agadir/3 samples using MA-30/MA-31 indicated their closest relationship (98.1% identity) was to the corresponding region of the TYLCV-Is isolate reported from Spain (GenBank Accession no. AF071228). Based on the hybridization and sequence data, we conclude that the symptomatic plants from Gran Canaria were infected by TYLCV-Sar, those from Agadir/1 and Agadir/2 were infected by TYLCV-Is, and those from Agadir/3 had mixed infections with TYLCV-Is and TYLCV-Sar. The presence of TYLCV-Is in Morocco has been described recently (2). However, this is the first report of TYLCV-Sar in the Canary Islands and Morocco and extends its geographic range beyond the Iberian Peninsula and Italy. References: (1) J. Navas-Castillo et al. Plant Dis. 83:29, 1999. (2) M. Peterschmitt et al. Plant Dis. 83:1074, 1999. (3) S. Sánchez-Campos et al. Phytopathology 89:1038, 1999